Implementation of Direct and Indirect Learning Strategies in English Vocabulary Learning at Pittayaphat Suksa School, Thailand - Sya, Mega Febriani; Ridwan, Muhammad; Kholik, Abdul; MIRKH, Abdul Meatam (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2025)
Good vocabulary mastery can be achieved by applying the right strategy in the learning process. An effective strategy will help students in improving their ability to master English vocabulary well and quickly. The purpose of this study is to find out the English vocabulary learning strategies and teaching materials used by teachers in learning English vocabulary at Pittayaphat Suksa School. The research approach is qualitative with case study research type. The case study was conducted to conduct intensive, detailed and in-depth study of learning strategies at Pittayapaht Suksa School to understand a learning culture that occurs at Pittayaphat Suksa School. The data collection techniques used were observation, interview and documentation obtained from the community at Pittayaphat Suksa School. Data were analyzed by reducing relevant data, presenting data, and drawing conclusions. The results of this study show that in learning English vocabulary teachers use direct learning strategies to enrich vocabulary and improve students' English pronunciation and indirect learning strategies to improve students' mastery of English vocabulary and grammar.